User-centered workspace design understanding design preferences based on the disc temperaments of urban office workers - Catipay, Jhemima R. (2021)
This study aimed do determine whether the DISC temperaments of the office workers of DENR Region XI have an influence over their office layout and wall and floor finishes preferences.A survey using the DISC Model of Human Behavior and Office Design Preferences were administered by the researcher to the respondents. Upon analyzing the gathered data, the major findings showed that aside from the DISC temperaments of the respondents, the DENR's nature of being a service-oriented organization affected their office layout preferences. Additionally, their floor and wall finish preferences were heavily influenced by their perception of color with regards to their working environment, instead of their DISC temperaments. A survey using the DISC Model of Human Behavior and Office Design Preferences were administered by the researcher to the respondents. Upon analyzing the gathered data, the major findings showed that aside from the DISC temperaments of the respondents, the DENR's nature of being a service-oriented organization affected their office layout preferences. Additionally, their floor and wall finishes preferences were heavily influenced by their perception of color with regards to their working environment, instead of their DISC temperaments.